Rancang Bangun Aplikasi Ensiklopedia Digital Tanaman Obat Tradisional - Gosal, Silvia Siladevi; Lestari, Ariesta; Nugrahaningsih, Nahumi (Journal of Information Technology and Computer Science, 2023)
The lack of available documentation to store information about traditional medicinal plants has made it increasingly difficult to obtain information about medicinal plants. Therefore, in this research, an Encyclopedia of Medicinal Plants of Borneo (E-TOB) application is designed to be a readily accessible source of information for users, both through a website and a mobile application.The development of the E-TOB application follows the stages of the Waterfall method, starting from the Requirements Definition stage depicted using Flowchart, the Requirements Analysis and Definition stage depicted through UML (Unified Modeling Language) with Use case Diagram, Class diagram, and Activity diagram, as well as the use of a database. Implementation and Unit Testing are done using Laravel, Flutter, and MySQL frameworks, and testing is conducted using the Blackbox method. In the developed application, the admin has access to manage the data of medicinal plants.The built application has three (3) types of users, namely guest users, who can view information about medicinal plants. Admin users who have access to manage data in the application, and registered users who can add medicinal plants and access additional features in the application such as bookmark and like features.